DURABILITY OF LIME STABILIZED EARTH BLOCKS - GUETTALA, A; HOUARI, H.; MEZGHICHE, B.; CHEBILI, AND R. (Courrier du Savoir; مجلد 2 (2002): Courrier du Savoir, 2014)
The main drawback of earth construction is the rapid deterioration of the material under severe weather conditions. The objective of this work is to improve the behaviour of stabilised blocks of earth blocks against water attacks. The blocks manufactured with one type of earth were tested in compressive strength as dry blocks and after immersion, in intensive sprinkling and in absorption. Tests of wetting-drying. The tests of freeze- thaw were also carried out. The results show the influence of the different manufacturing parameters: compacting intensity, sand content and lime content on the mechanical strength in the dry state as well as in the wet state, water resistance coefficient, the weight loss and the absorption.